2014
DOI: 10.1161/strokeaha.113.004229
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic Dyslipidemia and Residual Cardiovascular Risk in Statin-Treated Patients

Abstract: Background and Purpose-Treatment with statins reduces the rate of cardiovascular events in high-risk patients, but residual risk persists. At least part of that risk may be attributable to atherogenic dyslipidemia characterized by low highdensity lipoprotein cholesterol (≤40 mg/dL) and high triglycerides (triglycerides ≥150 mg/dL). Methods-We studied subjects with stroke or transient ischemic attack in the Prevention of Cerebrovascular and Cardiovascular Events of Ischemic Origin With Terutroban in Patients Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
44
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 44 publications
7
44
0
1
Order By: Relevance
“…6 Also, among 3 major studies comprising over 30,000 subjects with stroke or transient ischemic attack, approximately 10% of subjects had remaining atherogenic dyslipidemia (low HDL-C and high triglycerides) after statin therapy, and these subjects had excess cardiovascular risk. 7 Importantly, Mora et al 16 reported in the JUPITER trial that despite potent statin therapy, on-treatment levels of LDL-C, non-HDL-C, and apoB remain significant predictors of residual CVD event risk, although diminished once on-treatment LDL-C levels of ,70 mg/dL, non-HDL-C levels of ,100 mg/dL, or apoB levels of ,80 mg/dL are attained. Of note, Ballantyne et al 15 have noted that during statin therapy in higher risk patients, it is necessary to reduce the non-HDL-C to ,100 mg/dL (or LDL-C to ,70 mg/dL in higher triglyceride or ,80 mg/dL in lower triglyceride patients) to reach an apoB target of even ,90 mg/dL and that a close correspondence of ApoB with non-HDL-C while on statin therapy suggested the latter would be a good surrogate for apoB levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Also, among 3 major studies comprising over 30,000 subjects with stroke or transient ischemic attack, approximately 10% of subjects had remaining atherogenic dyslipidemia (low HDL-C and high triglycerides) after statin therapy, and these subjects had excess cardiovascular risk. 7 Importantly, Mora et al 16 reported in the JUPITER trial that despite potent statin therapy, on-treatment levels of LDL-C, non-HDL-C, and apoB remain significant predictors of residual CVD event risk, although diminished once on-treatment LDL-C levels of ,70 mg/dL, non-HDL-C levels of ,100 mg/dL, or apoB levels of ,80 mg/dL are attained. Of note, Ballantyne et al 15 have noted that during statin therapy in higher risk patients, it is necessary to reduce the non-HDL-C to ,100 mg/dL (or LDL-C to ,70 mg/dL in higher triglyceride or ,80 mg/dL in lower triglyceride patients) to reach an apoB target of even ,90 mg/dL and that a close correspondence of ApoB with non-HDL-C while on statin therapy suggested the latter would be a good surrogate for apoB levels.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] A recent analysis of several large clinical trials shows that subjects with remnant atherogenic dyslipidemia despite statin therapy had increased CVD event rates. 7 US population-based data on the proportion of individuals specifically on statins who are not at goal for LDL-C and other lipids and the distribution of the extent of deviation from goal have not been reported. In this report, we examine among US adults on statin-based therapy, the proportions of individuals with LDL-C, non-HDL-C, or apolipoprotein B (apoB) not at recommended levels and the discordance of goal attainment between these fractions.…”
Section: Introductionmentioning
confidence: 99%
“…However, atherogenic dyslipidemia as defined by HDL-C ≤ 40 mg/dL and TG ≥150 mg/dL has been associated with greater risk of recurrent stroke 90 days after a transient ischemic attack (TIA), 4 and with higher residual cardiovascular risk among ischemic stroke and TIA patients receiving statin therapy. 20 …”
Section: Discussionmentioning
confidence: 99%
“…2 Although the cholesterol-lowering action of statins has been consistently shown to translate into fewer cardiovascular events, [3][4][5] residual risk persists in a large proportion of statintreated individuals as a result of either an inability to achieve desirable LDL levels 1,6,7 or the presence of other traits that predispose to CVD, including low high-density lipoprotein (HDL) or high plasma triglycerides. 8,9 Moreover, intolerance to statins manifested principally as myopathy, with a spectrum ranging from myalgia to rhabdomyolysis, 10,11 and concerns about increased risk of new-onset type 2 diabetes mellitus with statin use 12,13 may result in discontinuation or suboptimal dosing of statins.…”
mentioning
confidence: 99%